ChemInform Abstract: Enhanced Thermoelectric Properties of Pb‐Doped BiCuSeO Ceramics. Issue 51 (17th December 2013) - Lan, Jin‐Le; Liu, Yao‐Chun; Zhan, Bin; Lin, Yuan‐Hua; Zhang, Boping; Yuan, Xun; Zhang, Wenqing; Xu, Wei; Nan, C.‐W.
Abstract Bi1‐xPbxCuSeO (x = 0—0.08) samples are prepared by solid state reaction of Bi2O3, PbO, Cu, Bi, and Se (573 K for 6 h and 973 K for 10 h).